Commercial diplomacy in international entrepreneurship a conceptual and empirical exploration - Ruël, Huub (Advanced series in management ;, 2012)
Little attention has been devoted to the topic of commercial diplomacy, defined as the application of diplomacy to help bring about specific commercial gains through promoting exports, attracting inward investment and preserving outward investment opportunities, and encouraging the benefits of technology transfer. The spectrum of actors in commercial diplomacy ranges from the high-policy level (head of state or prime minister to ambassador) and the lower level of specialized diplomatic envoys like trade representative, commercial attaché or commercial diplomat. This volume focuses on how to organize diplomacy to support international entrepreneurs. It takes an interdisciplinary perspective, combining the fields of business administration and public administration, more specifically international entrepreneurship and international relations. This is the first interdisciplinary book that extensively explores the organization of diplomacy for international entrepreneurship at the micro level: the diplomats' and individual entrepreneurs' perspective.